Optimization of Chicken Feed Distribution Using Least Cost and Modified Distribution Method at PT. Mabar Feed Indonesia - Astuti, Widya Tantri; Nasution, Hamidah; Husein, Ismail (UIN Sumatera Utara, 2021)
The optimization model is one of the systems analysis models identified with operation research. The transportation method is part of a linear program that is used to organize and distribute resources that provide products to places where they are needed to achieve transportation cost efficiency. The working principle of the Least Cost method is to give allocation priority that has the smallest unit cost (the smallest unit cost). The MODI (Modified Distribution) method is a method of solving transportation cases developed from the Stepping Stone method. This research was conducted at PT. Mabar Feed Indonesia which is engaged in the feed sector. This study aims to determine minimizing transportation costs at PT. Mabar Feed Indonesia which will later become input for the company. The results showed that the transportation cost before minimization was Rp . Then the costs incurred after using the Least Cost method in the initial solution amounted to Rp . After using the Least Cost method, the final solution is to make MODI more optimal and the total transportation cost is Rp .